2008
DOI: 10.2164/jandrol.107.002592
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of 6 Unrelated Italian Patients With 5α‐Reductase Type 2 Deficiency

Abstract: Steroid 5a-reductase (5aR) deficiency (OMIM number #264600) is a rare 46,XY disorder of sex differentiation caused by mutations in the 5aR type 2 gene (SRD5A2) resulting in dihydrotestosterone deficiency during fetal development. We report on the analysis of the SRD5A2 gene in 6 unrelated 46,XY Italian patients with external genitalia morphology ranging from predominantly female to nearly completely male. Three subjects were seen and assessed at birth, 1 patient was referred to us before puberty, and 2 at post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 39 publications
4
29
1
2
Order By: Relevance
“…Though the first proposed value was 20, Walter et al suggested 8.5 after hCG stimulation as a much more reliable cutoff value [24,64,65]. However, in many instances, this method has failed as a good predictor and various other approaches have been proposed [22,39,41,45,49], urinary steroid profiling (UPS) and gene mutation analysis being two alternatives. Chan et al suggested that UPS results can be misinterpreted; thus, molecular [25,39,40] p.G115D/p.G115D 5 2.60 0.55 [22,39,41,42] analysis was considered the most effective diagnostic method also taking into account the small size of the gene makes the diagnostic procedure easier [50].…”
Section: Diagnosismentioning
confidence: 99%
“…Though the first proposed value was 20, Walter et al suggested 8.5 after hCG stimulation as a much more reliable cutoff value [24,64,65]. However, in many instances, this method has failed as a good predictor and various other approaches have been proposed [22,39,41,45,49], urinary steroid profiling (UPS) and gene mutation analysis being two alternatives. Chan et al suggested that UPS results can be misinterpreted; thus, molecular [25,39,40] p.G115D/p.G115D 5 2.60 0.55 [22,39,41,42] analysis was considered the most effective diagnostic method also taking into account the small size of the gene makes the diagnostic procedure easier [50].…”
Section: Diagnosismentioning
confidence: 99%
“…However, equivocal or false-negative T/DHT results are not uncommonly reported (2)(3)(4)(5)(6). Alternative approaches in diagnosing 5ARD include the use of urinary steroid profiling (USP) (7 ) and mutational analysis of SRD5A2 (8 ).…”
Section: ␣-Reductase 2 Is a Membrane-bound Nadphdependent Microsomalmentioning
confidence: 99%
“…[20] Gen seviyesinde erkek infertilitesi, protamin gen mutasyonları [21,22] , 5-alfa redüktaz eksikliği [23] , androjen reseptörü gen mutasyonları [24,25] ve CFTR gen mutasyonlarıyla bağlantılıdır.…”
Section: Discussionunclassified